Dual tuned 1H/31P quadrature microstripline-based transmit/receive switch for 7 Tesla magnetic resonance imaging - Ashraf Abuelhaija; Gameel Saleh (Institute of Advanced Engineering and Science, 2022)
A dual tuned transmit/receive (T/R) Switch for 7 tesla magnetic resonance imaging (MRI) that is based on concentric microstripline (MSL) coupler is introduced. The proposed switch is designed using two concentric MSL quadrature couplers on the top and bottom faces of the switch. The switch can be used to handle two frequency signals to/from two radio frequency (RF) coils. In this article, a 1H/31P atomic nuclei are excited. The two MSLs on the upper face of the switch are designed to transmit 298 and 120.6 MHz signals into RF coils, whereas each of the identical upper and lower MSLs are used to receive these signals from the RF coils. This switch can be used to transmit/receive signals from two RF coils at the same time, one work with 1H and the second with 31P atomic nuclei, and without any tuning. The proposed switch has been designed and simulated using the electromagnetic microwave studio computer simulation technology (CST). It demonstrates good matching (≈17 dB), low insertion loss (≈0.3) and high isolation (>70) for the 1H and 31P magnetic resonance signals at transmit mode. During receive mode, It demonstrates good matching (>20 dB), low insertion loss (≈0.2) and high isolation (>70) for the 1H and 31P magnetic resonance signals.